2018
DOI: 10.3346/jkms.2018.33.e298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hepatic Cytochrome P450 3A Activity Using Metabolic Markers in Patients with Renal Impairment

Abstract: BackgroundThe renal function of individuals is one of the reasons for the variations in therapeutic response to various drugs. Patients with renal impairment are often exposed to drug toxicity, even with drugs that are usually eliminated by hepatic metabolism. Previous study has reported an increased plasma concentration of indoxyl sulfate and decreased plasma concentration of 4β-hydroxy (OH)-cholesterol in stable kidney transplant recipients, implicating indoxyl sulfate as a cytochrome P450 (CYP) inhibiting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Many anticancer drugs are predominantly metabolized by the liver CYP3A enzyme (Tables 1 and 2 ). The pharmacokinetics of CYP3A4/5 model drugs showed relatively smaller changes to CKD [155, 156], which is supported by the results that hepatic CYP3A activity was not affected by renal impairment-induced accumulation of plasma indoxyl sulfate [157], although uremic plasma from subjects with ESRD was reported to inhibit the metabolism of the CYP3A probe midazolam in human liver microsomes from donors with normal renal function [87]. Consistent with these results [155, 156], no effect of renal impairment on the pharmacokinetics of the anticancer drugs predominantly metabolized by the liver CYP3A was observed: (1) cytotoxic anticancer drug docetaxel (Table 3 ) and (2) most TKIs, but excluding cytotoxic eribulin, etoposide and paclitaxel, and TKIs of vandetanib and crizotinib.…”
Section: Mechanisms Underlying Modified Pharmacokinetics Of Non-renalmentioning
confidence: 83%
“…Many anticancer drugs are predominantly metabolized by the liver CYP3A enzyme (Tables 1 and 2 ). The pharmacokinetics of CYP3A4/5 model drugs showed relatively smaller changes to CKD [155, 156], which is supported by the results that hepatic CYP3A activity was not affected by renal impairment-induced accumulation of plasma indoxyl sulfate [157], although uremic plasma from subjects with ESRD was reported to inhibit the metabolism of the CYP3A probe midazolam in human liver microsomes from donors with normal renal function [87]. Consistent with these results [155, 156], no effect of renal impairment on the pharmacokinetics of the anticancer drugs predominantly metabolized by the liver CYP3A was observed: (1) cytotoxic anticancer drug docetaxel (Table 3 ) and (2) most TKIs, but excluding cytotoxic eribulin, etoposide and paclitaxel, and TKIs of vandetanib and crizotinib.…”
Section: Mechanisms Underlying Modified Pharmacokinetics Of Non-renalmentioning
confidence: 83%
“…Current evidence suggests that severe RI or ESRD may significantly affect the PK of drugs that are primarily eliminated by the liver, whereas the effects are not significant for mild and moderate RI ( 67 , 68 , 94 ). As shown in the present review, most TKIs are primarily eliminated via the liver, indicating that the effects of mild and moderate RI on the PK of most TKIs are not clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired renal function may decrease the excretion of a drug or its metabolites that are primarily or partly eliminated via the kidneys ( 9 , 58 ). In addition, RI may also affect the non-renal disposition of drugs that are eliminated by the liver via alterations in the expression and activity of drug-metabolizing enzymes and transporters in the liver ( 67 , 68 ). Although the most obvious changes with RI affect the elimination of drugs as well as their metabolites, RI may also be associated with other changes, such as absorption and PB ( 9 ).…”
Section: Dose Adjustment For Patients With Rimentioning
confidence: 99%
“…The concentrations of four urinary steroids (cortisol, 6b-OHcortisol, cortisone, and 6b-OH-cortisone) and one plasma steroid (4b-OH-cholesterol) were quantified using a 7890B series gas chromatograph (Agilent Technologies, Santa Clara, CA) coupled with a 7000B series triple quadrupole mass spectrometer (Agilent Technologies, Santa Clara, CA) as described previously (Kim et al, 2018a). The ratio of 6b-OHcortisol/cortisol and 6b-OH-cortisone/cortisone, and concentration of 4b-OH-cholesterol, were calculated and used as markers for the measurement of CYP3A activity.…”
Section: Endogenous Markers For Cyp3a Activitymentioning
confidence: 99%
“…Moreover, secondary bile acids are mainly biotransformed by gut bacterial species and previous studies have shown that oral administration of vancomycin alters fecal bile acids concentration. Therefore, we hypothesized that oral vancomycin-induced dysbiosis of the gut microbiota could cause the disruption of CYP3A activity and that this could be evaluated through the analysis of CYP3A activity and expression using well-known and validated metabolic markers described in previous studies (Lee et al, 2017;Kim et al, 2018b;Kim et al, 2018a;Lee et al, 2021). Since antibiotics are extensively used in various disease, screening of the gut bacteria indirectly responsible for affecting CYP3A activity will provide valuable insight for the development of personalized medicine in the future (Behrouzi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%